Efficacy of antidepressants in functional dyspepsia: Systematic review and meta-analysis with trial sequential analysis of randomized controlled trials - Shanmugham, Suresh; Mohammed Zuber; Chan, Jia En; Kumar, Suresh; Ching, Siew Mooi; Lee, Yeong Yeh; Vadakkechalil, Harsha; Veettil, Sajesh K. (Springer, 2024)
Introduction: The beneficial effects of using antidepressants in improving functional dyspepsia (FD) symptoms have been reported in previous meta-analyses; however, the results have not been conclusive. The aim was to perform an updated meta-analysis coupled with trial sequential analysis (TSA) to assess the efficacy of the use of any antidepressants in the treatment of FD in adults. Methods: Electronic databases were searched up to March 2024 for randomized controlled trials (RCTs) recruiting adults with FD. Data of overall symptoms improved between the antidepressants and placebo groups was pooled to obtain risk ratio (RR) employing the random-effects model. The effect of random errors was evaluated with TSA. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to assess the certainty of evidence. Analyses were performed using STATA version 16.0. Results: Nine RCTs with 924 patients met the eligible criteria. The RRs of FD symptoms improving with any antidepressants, tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors were (n = 9, RR = 1.30 [95% CI, 1.02-1.67]), (n = 5, RR = 1.41 [95% CI, 1.07-1.85]) and (n = 2, RR = 0.97 [95% CI, 0.72-1.29]), respectively. TSA demonstrated conclusive evidence for the beneficial effect of TCAs. The number needed to treat (NNT) with any depressants and TCAs were 11 (95% CI, 7-36) and 6 (95% CI, 4-15), respectively. The certainty of the evidence for an effect of TCAs was that of moderate GRADE quality. The benefit, however, was limited to the western population (n = 3, RR = 1.43 [95% CI, 1.04-1.96]) and did not extend to the Asian population (n = 2, RR = 1.32 [95% CI, 0.75-2.32]). Conversely, antidepressant-using patients experienced adverse events more frequently. However, no statistically significant association was found between TCAs and any adverse events (n = 3; RR = 1.36 [95% CI, 0.91-2.04]). Conclusion: Evidence was obtained suggesting TCAs can be an effective alternative in the treatment of FD, but more evidence from high-quality large trials is required to support their use, especially in the Asian population.